2021
DOI: 10.1002/lpor.202100117
|View full text |Cite
|
Sign up to set email alerts
|

Doubly‐Resonant Enhancement of Second Harmonic Generation from a WS2 Nanomesh Polymorph with a Modified Energy Landscape

Abstract: Although transition metal dichalcogenides (TMDs, e.g., WS2, WSe2, MoS2, MoSe2) have emerged as highly promising 2D materials for nonlinear optics, they are limited by intrinsically small light‐matter interaction length and (typically) flat‐lying geometries. The first hyperspectral multiphoton analysis of a tridimensional webbed network of densely‐packed stacks (of 1–5 layers) of twisted and/or fused 2D nanosheets of WS2, referred to as “nanomesh”, is presented here. The optical second harmonic generation (SHG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 72 publications
(111 reference statements)
0
7
0
Order By: Relevance
“…[21] As a result, providing a sophisticated optical design for the use of TMDCs in nonlinear processes is critical. Recent studies suggest using different TMDC morphologies, such as nanomesh, [22] tubular, [23] and nanoporous [24] networks. Despite the excellent findings of these studies, these nanostructures are challenging to incorporate into optical circuits.…”
Section: Introductionmentioning
confidence: 99%
“…[21] As a result, providing a sophisticated optical design for the use of TMDCs in nonlinear processes is critical. Recent studies suggest using different TMDC morphologies, such as nanomesh, [22] tubular, [23] and nanoporous [24] networks. Despite the excellent findings of these studies, these nanostructures are challenging to incorporate into optical circuits.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a giant SHG response could be observed in the Janus ReSSe monolayer due to structural symmetry breaking-induced large second-order nonlinear coefficient. In general, the second-order nonlinear optical response processes mainly divided into non-resonant transition, single-resonant transition, and doubly-resonant transition in an energy landscape. , Meanwhile, in our previous work, , it has been confirmed that the prominent peak in the second-order nonlinear dispersion relation originates mainly from the resonant transition processes at the high-symmetry point or along the high symmetry line in the band structure for a semiconductor. In the present work, the electronic band structure of the Janus ReSSe monolayer possesses a smaller curvature, which can lead to more resonant effects including both single-resonant transition and doubly-resonant transition processes.…”
Section: Resultsmentioning
confidence: 80%
“…The broad available band of the SHG signal from the MoSe 2 spiral should arise from the resonance enhancement effect of C exciton, since the C exciton was reported to show broadband feature, i.e., ≈10 times broader than that of the A and B excitons in monolayer MX 2 as reported previously based on theoretical calculations and experiments. [40] Considering that the C exciton of MX 2 is associated with multiple transitions from the Γ−Κ line of the Brillouin zone (i.e., from band nesting effect), as also evidenced by the WS 2 nanomesh, [41] certain energy transitions within the whole test range should contribute to the broad available band of the SHG signal from the MoSe 2 spiral.…”
Section: Resultsmentioning
confidence: 99%